FINANCIAL DISTRESS AND OTHER FINANCIAL CONDITIONS ON GOING CONCERN AUDIT OPINIONS - Agus Salim (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to examine the effect of Financial Distress, Leverage, Solvency, Profitability and Liquidity on Going Concern Audit Opinions. This research uses company data listed on the IDX and consistently enters the group of manufacturing companies from 2019-2021. This study uses a logistic regression analysis tool using SPSS to answer the proposed hypothesis. The results showed that Financial distress had an effect on going-concern audit opinion, Leverage had no effect on going-concern audit opinion, Solvability had no effect on going-concern audit opinion, Profitability had no effect on going-concern audit opinion, Liquidity had no effect on going-concern audit opinion